Working with data in the public sector : from fear to enthusiasm - McIntyre-Lahner, Anne; Schack, Ronald W. (New York : Routledge, 2025)
"Working with Data in the Public Sector: From Fear to Enthusiasm is the first book designed for practicing and future public administration professionals to help overcome any anxiety about using data effectively in their roles. Authors Anne McIntyre-Lahner and Ronald Schack explore different types and degrees of data fear (a data fear/data comfort continuum) and provide a tool-box of fear-fighting techniques, including methods of dealing with data fear "in the moment," methods of mitigating data fear related to using, sharing, and reporting data, and demonstrating how many common data tasks need not be scary. They further offer a self-assessment instrument and process to help individuals assess their level of data fear/comfort, identifying which specific dimensions of data fear/comfort may be most problematic at both the individual and organizational level. The book examines how individual data fear can "infect" organizations, collaboratives, and communities, and how to "bake in" data fear prevention in one's efforts to create and sustain a data-informed culture. It is important reading for both practicing and future public servants, including those enrolled in Public Administration, Public Policy, and Nonprofit Management programs"--
Part I: The nature of data fear -- The nature of fear -- Stages of data comfort -- Fear related to capacity -- Fear related to use -- Part II: Assessing our abilities and anxieties about data -- A fear self-assessment -- Part III: Addressing and overcoming data fear: taming the fear monster -- A fear-fighting toolbox -- Analysis doesn't have to be scary -- Approaches to reducing fears related to use -- Part IV: Moving beyond individual data fear -- Organizational data fear -- Collaborative data fear -- Creating and sustaining a data-informed culture -- Data fear and the application of evidence-based and promising practices -- Community data fear and data responsibility -- Data rear and DEIA (Diversity, Equity, Inclusion, and Accessibility) -- The promise and perils of the use of artificial intelligence in data analysis and reporting -- An interview with the authors.
Keywords: Public administration -- Data processing -- Management; Information resources management; POLITICAL SCIENCE / Public Affairs & Administration; POLITICAL SCIENCE / Public Policy / General